Linear and V‐Shaped Alkynyl‐1, 3, 5‐triazines. Issue 32 (2nd October 2015) - Gao, Peisen; Wang, Zhenhua; Wang, Xiu; Zhang, Weiqiang; Gao, Ziwei
Abstract: A concise route for the synthesis of linear and V‐shaped alkynyl‐1, 3, 5‐triazines has been developed by starting from 2, 4‐dichloro‐1, 3, 5‐triazine derivatives. The sequential substitution of the 2‐ and 4‐chloro groups by a regioselective Sonogashira coupling reaction afforded symmetric and unsymmetric V‐shaped alkynyl‐1, 3, 5‐triazines. A modulated copper‐free Pd/1, 10‐phenanthroline catalyst system showed good compatibility with the –OCH3, –NPh2, and p ‐CH3 OC6 H4 – substitutents and furnished the targeted linear alkynyl‐1, 3, 5‐triazines in good yields. A Pd/Ag bimetallic system afforded the desired symmetric and unsymmetric V‐shaped alkynyl‐1, 3, 5‐triazines in moderate to good yields. The photophysical properties of the new alkynyl‐1, 3, 5‐triazine compounds were characterized experimentally. The X‐ray diffraction analysis of2a confirmed a coplanar position between the phenyl group and the 1, 3, 5‐triazinal moiety. Intermolecular π–π interactions were observed between two of the TZ units, and the shortest atomic contact distance between the phenyl moieties of two adjacent molecules is 3.655 Å. Abstract : A protocol has been developed for the synthesis of alkynyl‐1, 3, 5‐triazines, especially unsymmetrical alkynyl‐1, 3, 5‐triazines with two different alkynyl groups on the triazine core. The Pd2 (dba)3 /1, 10‐phenanthroline catalyst system was used in a copper‐free Sonogashira coupling reaction followed using a Pd/Ag bimetallic system for the subsequent alkynyl coupling step. dba = dibenzylideneacetone, 1, 10‐phen = 1, 10‐phenanthroline, DIPEA = N, N ‐diisopropylethylamine, and Tf = trifluoromethylsulfonyl.